ANALYSIS OF THE EFFICIENCY OF KARET JATIMLEREK DAM ON AGRICULTURAL IRRIGATION IN PLANDAAN DISTRICT, JOMBANG REGENCY - Nasirudin, Mohamad; Yuliana, Anggi Indah; Aviv, Romadhon Luqman (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
This study aims to determine the effectiveness of water distribution from the Jatimlerek Rubber Dam in irrigating agricultural land in Jatimlerek, Purisemanding, Karangmojo, and Plandaan Villages, Plandaan District, Jombang Regency. The method used is quantitative. The results obtained are the efficiency of distribution in the Jatimlerek secondary channel of 86.13%. Water loss along the Jatimlerek secondary channel is 0.38% of the efficiency in the secondary channel under normal conditions of 90%, so it can be concluded that Jatimlerek secondary irrigation is less effective. Water loss occurs due to the poor condition of the existing irrigation network lining. The conclusion based on the calculation of water loss and irrigation efficiency along the Jatimlerek secondary channel from BJM 2 - BJM 7 is that water loss is 0.38% and the efficiency of Jatimlerek secondary channel irrigation is 86.13%. Then the condition of the Jatimlerek secondary irrigation structure from BJM 2 - BJM 7 of the six BJMs observed, there were two BJMs that experienced damage to the secondary channels, namely BJM 5 located in Plandaan Village and BJM 7 in Purismanding Village which resulted in a decrease in the flow function.